Adversity Quotient in Mathematics Learning (Quantitative Study on Students Boarding School in Pekanbaru) - MZ, Zubaidah Amir; Risnawati, Risnawati; Kurniati, Annisah; Prahmana, Rully Charitas Indra (Universitas Ahmad Dahlan, 2017)
The aim of this study is to analyze studentsâ Adversity Quotient (AQ) in mathematics learning viewed from gender aspect. This study is quantitative survey study on students in MTs Al-Munawarah Boarding School, Pekanbaru. The subjects of study are 8th grade students consisting ofÂ 75 girls and 63 boys. Data are collected by AQ scale and analyzed with statistic descriptive and inferential (test-t). The indicator of AQ consist of control, origin, ownership, reach and endurance.Â The result of descriptive analysis shows that there is difference in mean of each indicator for two groups, but analysis of test-tÂ shows that there is no difference in studentsâ mathematical AQ for two group of gender. Through variance test, studentsâ mathematical AQ in two groups is homogeneous. The indicator of AQ in boys which is categorized as high are endurance and reach. While, the indicator in girls is aspect of control. This study contributes to literature study in identifying studentsâ AQ and the effort done to enhance studentsâ AQ in mathematics learning.